Some Methodological Methods Of Solving Issues From Quantum Physics (Texas Journal of Multidisciplinary Studies, 2022)
In this article, some aspects of the methodology for teaching the course “quantum mechanics” for theoretical training of students studying in the field of physics will be considered. In the study of”quantum mechanics", methods of adaptation of lecture materials, which are difficult to understand, in practical exercises, the application of quantum operators to the study of quantum systems, and the approach to probability are studied